Caste differences in Pseudopolybia compressa (Hymenoptera: Vespidae: Polistinae) - Pizarro, Laura Chavarría [UNESP]; Noll, Fernando Barbosa [UNESP]; Mateus, Sidnei (Sociedade Brasileira de Zoologia, 2009)
Studies of morphological caste syndromes in the tribe Epiponini help us to understand the evolution of social behavior in insects. Few studies have integrated morphological syndromes of various species from the same or distinct genera. We studied morphological differences between castes from three colonies of Pseudopolybia compressa de Saussure, 1854, in order to relate their caste syndrome with those of other species in the genus. We took eight morphometric measures and females were classified in relation to ovarian development and spermathecal contents. Females of Colony 1 (C1) present a higher distinction between castes than females of Colonies 2 and 3 (C2 and C3), and, in general, queens of the three colonies are larger than workers in some measures but smaller in others. In Pseudopolybia Dalla Torre, 1894, shape rather than size is a more important trait in caste divergence.
Keywords: Dimorphism; Epiponini; morphological syndromes; queen; shape; workers